The role of age in second language acquisition.: The role of age in second language acquisition. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2021)
Abstract: Whether starting learning foreign languages in the early age or not is an argumentative topic among most pedagogics and researchers. It is mostly believed that age is significant factor in learning foreign languages. While, others argue and advocate for imposing the learners to foreign languages a bit later is preferable. Studies also have shown that other factors play significant roles in this, varying from learning languages in natural way and by the help of instructor to settings in which language is learnt and the amount of time spent. So far, there has not been a definite finding suggesting the certain age or the right factors to start learning a foreign language which has resulted in a discussion on this matter. This paper intends to discuss how much age factor is important in learning foreign languages.